Developmental changes in memory structure and precision alter the use of retrieved episodes during decisions for reward - Nora C. Harhen; Aaron M. Bornstein; Catherine A. Hartley (Proceedings of the National Academy of Sciences, 2026)
Most widely studied option evaluation strategies rely on knowledge accumulated across repeated experiences. But how should options be evaluated in unfamiliar environments, in which knowledge is sparse? In these situations, how do decision makers make efficient use of limited past experience to guide their choices? One possible strategy is episodic sampling, in which a decision maker retrieves a small number of past decisions from memory to estimate the value of present options. By virtue of their age, children and adolescents have less experience than adults, making episodic sampling a particularly useful strategy for them. At the same time, the effectiveness of episodic sampling derives from memory’s precision and context sensitivity—properties that continue to develop into adolescence and young adulthood. This tension raises a key question: are developmental differences in episodic memory associated with differences in episodic sampling? To address this question, 106 participants, ages 8 to 25, completed a 2-d choice task that dissociated the influence of a single episodic memory from the influence of multiple episodes sharing a common context. At all ages, single episodes biased choices. But, only adults were sensitive to the broader evoked context. Further clarifying the relationship between episodic memory and decision making, differences in memory precision predicted differences in episodic sampling, even after taking into account age, while episodic sampling, in turn, accounted for individual differences in forward planning. Together, these findings suggest that episodic memory guides decision making throughout development, but the character of its influence evolves as memory becomes more precise and richly structured.